2017
DOI: 10.1186/s40168-017-0372-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the upper and lower respiratory tract microbiota in Piedmontese calves

Abstract: BackgroundThe microbiota of the bovine upper respiratory tract has been recently characterized, but no data for the lower respiratory tract are available. A major health problem in bovine medicine is infectious bronchopneumonia, the most common respiratory syndrome affecting cattle. With this study, we used 16S rRNA gene sequencing to characterize and compare the microbial community composition of the upper and lower respiratory tracts in calves.ResultsThe microbiota of the upper (nasal swab [NS]) and the lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 60 publications
(77 reference statements)
6
50
0
3
Order By: Relevance
“…The characterization of distinct niche microbiota throughout the bovine respiratory tract is a novel finding. Compositional differences between URT and lower respiratory tract (LRT) microbiotas have been previously observed in cattle [13][14][15]. However, these past studies have been limited in scope, comparing only trans-tracheal aspirations or bronchoalveolar lavages to the nasopharynx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characterization of distinct niche microbiota throughout the bovine respiratory tract is a novel finding. Compositional differences between URT and lower respiratory tract (LRT) microbiotas have been previously observed in cattle [13][14][15]. However, these past studies have been limited in scope, comparing only trans-tracheal aspirations or bronchoalveolar lavages to the nasopharynx.…”
Section: Discussionmentioning
confidence: 99%
“…The high abundance of Moraxella in the nasal passageways observed in the current study agreed with findings from previous research. Moraxella is often found to be one of the most abundant genera in the URT of cattle [14,[40][41][42]. The role of this genus in BP has been brought into question before, with one previous study finding an association between Moraxella and the development of pneumonia and/or otitis in early life of dairy calves [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, Bacteroidetes and Firmicutes predominate in humans, whereas Proteobacteria and Firmicutes predominate in mice. The respiratory microbiota has also been described in domestic animals (cats, dogs), and in farm animals (pigs, sheeps, and calves), which can serve as relevant translational models for humans ( Ericsson et al, 2016 ; Glendinning et al, 2016 ; Nicola et al, 2017 ; Siqueira et al, 2017 ; Vientos-Plotts et al, 2017a ).…”
Section: Composition Of the Lung Microbiotamentioning
confidence: 99%
“…Respiratory infection may be characterized into upper and lower respiratory tract infections (109). It has been revealed that air pollution PM may alter anti-mycobacterial respiratory epithelium innate immunity systems (110).…”
Section: Pm25-induced Pathogenesis In Respiratory Infectionmentioning
confidence: 99%